Formulation and Evaluation of Face Mist Preparation from Ethanol Extract of Agarwood Leaves (Aquilaria malaccensis L) as an Antioxidant - trijayanti, mesi; Pratiwi, Mida; Daskar, Annajim; Safutri, Wina (LPPM Universitas Dhyana Pura, 2025)
Skin damage due to UV exposure and pollution can trigger the formation of free radicals that accelerate the process of premature aging. The use of natural antioxidants in cosmetic products to combat free radicals serves as an alternative to synthetic antioxidants, which often cause side effects. Agarwood leaves (Aquilaria malaccensis L.) are known to contain groups of active compounds such as flavonoids, tannins, alkaloids, saponins, and terpenoids that have potential as antioxidants. This study aims to formulate and evaluate the face mist preparation of ethanol extract from agarwood leaves in three different concentration variations: FI (5%), FII (6%), and FIII (7%). The research was conducted experimentally in the laboratory, covering the stages of plant determination, maceration with 96% ethanol, phytochemical screening, formulation of preparations, physical evaluation (organoleptic, homogeneity, pH, specific gravity, spreadability, spray condition, drying time, protection, and stability through cycling tests), as well as antioxidant activity testing using the DPPH method with UV-Vis spectrophotometry. The results showed that all formulations had good physical characteristics and were stable using the cycling test method, except for FII which was unstable in the specific gravity test. The IC₅₀ values of each formulation were FI at 28.138 mg/L, FII at 21.871 mg/L, and FIII at 19.387 mg/L, categorized as very strong antioxidants and the three formulations had significant differences with a p-value of ˂0.05. The conclusion of this research is that the FIII formula (7%) is the best formula because it has high antioxidant activity, is stable physically and chemically, and has the potential as a natural cosmetic product that protects the skin from free radicals.